Palliative limb‐sparing photodynamic therapy with chemotherapy in a dog with osteosarcoma of the proximal tibia. Issue 4 (14th October 2018) - Osaki, Tomohiro; Murahata, Yusuke; Yamashita, Masamichi; Isao, Sakata; Okamoto, Yoshiharu
Abstract : Canine osteosarcoma conveys a poor prognosis. This long‐term follow‐up report describes using photodynamic therapy with intra‐arterial chemotherapy as palliation in canine osteosarcoma of the proximal tibia. A 10‐year‐old male Boston terrier dog presented with right hindlimb lameness; osteosarcoma of the right tibia was diagnosed. The owner chose palliative limb‐sparing photodynamic therapy with intra‐arterial chemotherapy. Right hindlimb lameness disappeared 24 days after the first treatment. In total, 210 days after the first treatment, post‐contrast T1 ‐weighted MRI showed a decreased gadolinium‐enhancing area within the tumour. And 254 days after the first treatment, the dog underwent the tenth treatment. Then 287 days after the first treatment, abdominal radiography showed an approximately 6‐ cm iliac lymph node. The dog died 321 days after the first treatment; lameness did not recur. Palliative photodynamic therapy with chemotherapy can be viable and feasible in osteosarcoma of the proximal tibia; more research is needed.